Web development productivity improvement through object-oriented application framework - Mohammad Nuruzzaman (2014)
Most of the commercial and industrial web applications are complex, difficult to implement, risky to maintain and requires deep understanding of the requirements for customization. As today's software market is more competitive, productivity has become a major concern in software development industry. The aim of this research is to design and develop an application framework for accelerating web development productivity through object-oriented technology. It allows customization, design reuse and automatic code generation to support productivity improvement as a breakthrough solution for the given problem. This research employed systematic literature review (SLR) to identify the source of complexity and productivity factors. Agile development methodology was used to design the framework and it was validated by empirical data from two commercial projects. Results showed that object-oriented application framework (OOAF) has significant factors that affect productivity and dramatically improve higher productivity over traditional approach. It has fulfilled the current needs by reducing complexities, development efforts and accelerates web development productivity. This research contributes in the area of software engineering, specifically in the field of software productivity improvement and software customization. These will lead to faster development time for software industries.